MUTU PELAYANAN DAN KEPUASAN PASIEN DI INSTALASI RAWAT INAP RUANG DAHLIA RSUD KOTA MADIUN - Suhadi Prayitno (Jurnal Kesehatan Manarang, 2017)
Service efforts undertaken by the Hospital was to improve the quality of health services quality and affordable by the community in order to improve public health status.Quality of service should be done by Hospital to improve patient satisfaction as a service user. The objective was to analyze association between service quality and patient satisfaction at Dahlia room,Regional Public Hospital Madiun .An observational analysis was conducted with cross-sectional study design. Samples were 78 using purposive sampling techniques. Data were analyzed by chi-square. This study showed that 56,4% respondents said that the quality of service was good. There were 52,6% respondents not satisfied with quality of service. Bivariate analysis showed association between service quality and patient satisfaction (p=0,014). There were an association between service quality and patient satisfaction. Madiun City General Hospital should improve the quality of service so that all patients are satisfied with the services provided.